IDENTIFICATION OF STRATIGRAPHIC TRAPS IN SANDSTONE RESERVOIRS X AND Y, TALANG AKAR FORMATION NIRU FIELD SOUTH SUMATERA BASIN - Septario Tempessy, Albert
Hydrocarbon explorations in the structural traps have been carried out in South Sumatera Basin for a long time, therefore it is necessary to conduct a study of other types of traps to discover new hydrocarbon reserves. It was already found reservoirs that produce oil with large reserves in Niru Field are Sandstone X and Y. Studies of geological modeling are necessary to understand the existing traps; and the method applied in this research is using multi-attribute seismic and static reservoir modeling. Some geological modeling phases conducted include: analysis of core and cutting description, Gamma Ray log analysis and performed “training” in multi-attribute seismic. A petrophysical analysis was performed to obtain reservoir property values which are shale volume and porosity. These values for each well were then distributed throughout the field using geostatistical method. All of these reservoir modeling results include the geometry and reservoir quality based on integration of well data and seismic attributes. This research conclude that generally Sandstone X and Y were deposited in fluvial-deltaic environment relatively in northeast-southwest direction. The integration of core data, cutting and Gamma Ray log yielded depositional facies of the reservoirs; distributary channel, meandering channel, sand bar, tidal channel, marsh and flood plain. Overlaying result of depth structure map and seismic attributes leads to a conclusion that there are stratigraphic traps with hydrocarbon prospect. The petrophysical analysis generated total porosity ranging from 0 to 29% and effective porosity ranging from 0 to 24%. From the distribution of total porosity and effective porosity values it can be concluded that the large porosity values are generally in the part of stratigraphic traps of the research area.